Dr. Chatpong Sastarasadhit — Deep Plane Facelift — Bangkok - Sastarasadhit, Chatpong (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Chatpong Sastarasadhit, practicing in Bangkok, Thailand. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003078; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; thailand; bangkok